ANALYSIS OF THE GENETIC HOMOGENEITY OF Bacillus anthracis VACCINE STRAINS STI-1 AND B. anthracis 55-VNIIVViM BY MLVA-25 - Kairzhanova , A.D.; Karibaev , T.B.; Shvedyuk , V.B.; Tyulegenov , S.B.; Zharova , M.K.; Shevtsova , E.S.; Kuibagarov , M.A.; Shevtsov А.B. (Eurasian Journal of Applied Biotechnology, 2017)
Determining the genetic stability of the causative agent of anthrax requires analysis of highly variable regions of DNA, including tandem repeats. Analysis of 25 loci with tandem repeats (MLVA-25) is a highly discriminating method used to genotype field strains of Bacillus anthracis, and allows the geographical distribution of genotypes to be tracked. This method can be easily applied to control the genetic stability of vaccine strains and strain identification. However, to date, there is no data about the genotypes of MLVA-25 vaccine strains used for vaccination in countries of the Commonwealth of Independent States. Here, using MLVA-25, we genotyped vaccine strains of B. anthracis STI-1 and B. anthracis 55-VNIIVViM that were deposited by three individuals from Kazakhstan. MLVA profiles of the individual vaccine strains obtained were identical, irrespective of the source. B.anthracis STI-1 and B. anthracis 55-VNIIVViM differed only in a single tandem repeat at the pXO1aat locus. Comparison of MLVA profiles obtained in this study with those obtained by in silico analysis of whole genome data revealed a discrepancy at the Bam22 and Bam23 loci in both B. anthracis STI-1 and B. anthracis 55-VNIIVViM, and at the Bam5 and Bam24 loci of B. anthracis STI-1.This study shows that MLVA analysis is highly discriminatory and can be used for quality control analysis of vaccine preparations. Moreover, standardization of the procedure for commercial application would require the analysis of typical crops.